THE IMPACT OF THE ARABIC CLUB EXTRACURRICULAR ACTIVITIES ON THE ENHANCEMENT OF SPEAKING PROFICIENCY (MAHARAH KALAM) AT SMPS MUHAMMADIYAH 01 MEDAN - Aini, Nur; lubis, zulfahmi (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
Speaking skill (Maharah Kalam ) is one of the essential competencies to be mastered in Arabic language learning. However, it often does not receive sufficient attention in formal Arabic language classes. Therefore, extracurricular activities such as the Arabic Club are seen as an effective solution to develop Arabic language skills, particularly Maharah Kalam. This study adopts a quantitative approach using a survey method and data analysis conducted through the SPSS application. The research sample consisted of 38 students who actively participated in the Arabic Club extracurricular program at SMPS Muhammadiyah 01 Medan. The results indicate a positive and significant influence between students' active participation in the Arabic Club and their speaking skill (Maharah Kalam). This study highlights that practice-based learning outside the classroom, such as through extracurricular programs li ke the Arabic Club, plays an important role in enhancing students' Arabic speaking abilities at SMPS Muhammadiyah 01 Medan.